Maternal and neonatal factors associated with low birth weight among neonates delivered at the University of Gondar comprehensive specialized hospital, Northwest Ethiopia - Dagnew Getnet Adugna; Misganaw Gebrie Worku (Frontiers Media S.A., 2022)
IntroductionLow birth weight is a major contributory factor to infant mortality. Although low birth weight remains an important public health problem in Ethiopia, little emphasis is paid to its intervention as a means of reducing neonatal mortality. The aim of this study was to assess the magnitude of low birth weight and its associated maternal and neonatal factors in newborns delivered at the University of Gondar Comprehensive Specialized Hospital.MethodsHospital-based cross-sectional study was conducted, and 481 study participants were selected using systematic random sampling methods. Pre-tested interviewer-administered questionnaires were used to collect the data. Bivariable and multivariable binary logistic regression was implemented. Finally, the odds ratio with a 95% CI and a p-value of <0.05 were used to identify factors associated with low birth weight.ResultThe prevalence of low birth weight was 12.5% (95% CI; 9.8, 15.7%). Preterm birth (AOR = 38; 95% CI: 15.3, 93.0), pregnancy-induced hypertension (PIH) (AOR = 2.6; 95%CI: 1.1, 6.4), maternal body mass index (BMI) of < 18.5 kg/m2 (AOR = 6.8; 95% CI: 1.5, 31.1), and grand multiparity (AOR = 4.2; 95% CI: 1.2, 16) were factors positively associated with low birth weight. However, babies delivered from mothers with age > 35 years (AOR = 0.14:95% CI 0.03, 0.7) had lower odds of low birth weight.ConclusionIn this study, the prevalence of low birth weight was higher than in the previous studies. The study revealed preterm birth, PIH, BMI of < 18.5 kg/m2, and grand multiparity were independent factors that increase the low birth weight while maternal age > 35 years reduces the low birth weight. Therefore, healthcare professionals should emphasize the early identification and management of women with PIH, tackling prematurity, and preventing maternal malnutrition through nutritional counseling as much as possible.